Manual Para Implantação De Banco De Pele Humana No Brasil - Steffen, Niveo [UNIFESP] (2018)
Introduction: The loss of integrity of large areas of skin caused by burns can result in severe pain, disability and can lead to death. The transplantation of human skin (allograft), although temporary, works as a biological dressing. Provide the conditions that allow the opening and operation of new skin and fundamental tissue banks for capturing, processing, storing and distributing thin slices of skin to be used as a transplant in the coverage of burned patients. Objectives: To elaborate a manual to guide and describe the stages and protocols necessary for the implantation of a Human Skin Bank in Brazil. Methods: Perform a bibliographic review on the subject based on normative references, national and international guidelines, published articles, medical journals, and online scientific article databases. The 10-year experience of practice of the Human Skin Bank of the Santa Casa de Misericórdia of Porto Alegre, Brazil, was used as theoretical and practical basis for the establishment and workings of a Skin Bank in Brazil. Results: The manual contemplated the survey of national and international tissue banks with their geographic distributions; history of allografts; describes the legal bases, infrastructure, processes and protocols of the tissue processing stages, observing standardization and validation of the procedures performed at the Skin Bank of the Santa Casa de Misericórdia of Porto Alegre. Conclusion: A manual for the implantation of a Human Skin Bank in Brazil was elaborated.